Ablation of atrial fibrillation in patient with an interatrial septal oclussion device - Montesinos-Segura, Renee (2023)
Interatrial septal occlusion devices hinder the transseptal approach for atrial fibrillation ablation,making it necessary to have imaging methods that safely guide transseptal puncture, such as intracardiac echocardiography (ICE). We describe the case of a 49-year-old patient with symptomatic paroxysmal atrial fibrillation, refractory to antiarrhythmic drugs, wearing an interatrial septal occlusion device, with a previous unsuccessful ablation attempt. Atrial fibrillation ablation was performed using the Carto V7 3D mapping system,  the transseptal puncture was guided by ICE, and the procedure was successful. This case report highlights the importance of multimodality imaging to achieve successful and effective transseptal puncture for atrial fibrillation ablation in patients with interatrial septal occlusion devices.